Abstract: A Spelling problem or „how to write“ phrases: „Holy Scripture“ or „Holy Scripture“, „Old Testament and New Testament“ or „Old Testament and New Testament“, placed in the context of the need for one-way pedagogical impact - Spasov, Chavdar (Forum Theologicum Sardicense, 2025)
Chavdar Spasov, Abstract: A Spelling problem or „how to write“ phrases: „Holy Scripture“ or „Old Testament“ and „New Testament“, placed in the context of the need for one-way pedagogical impact.